ANALISIS RASIO NET PROFIT MARGIN, RETURN ON ASSET, DAN INVENTORY TURNOVER TERHADAP PERUBAHAN LABA PADA PT. AKASHA WIRA INTERNASIONAL TBK. - UMRATUL HASANATUN; ARIS MUNANDAR; IMAM DARMAWAN (Universitas Mahasaraswati K. Mataram, 2024)
Increasing good performance can provide additional benefits for the company, where it attracts investors to increase capital in the hope that the company can develop well and generate optimal profits. Profit is an increase in an investor's wealth as a result of investment after deducting related costs. By using associative research methods, this research aims to determine the effect of net profit margin (NPM), return on assets (ROA), and inventory turnover (ITO) on changes in profits at PT. Akasha Wira Internasional Tbk. The research used a population of 16 years from 2007-2022, and the research sample was 10 years from 2012-2022 using the purposive sampling method. The analytical methods used include classical assumption tests, multiple linear regression analysis, correlation coefficients, and determination. Based on the hypothesis, the results of the analysis state that net profit margin does not have a positive effect on changes in profit, return on assets also does not have a positive effect on changes in profit, but inventory turnover has a positive effect on changes in profit. The results of the F test analysis show that there is a simultaneous influence between NPM, ROA and ITO on changes in profits, meaning that these three variables together have a positive effect on changes in profits